DETERMINANT FACTORS OF COVID-19 MORTALITY IN EAST JAKARTA IN 2021: Faktor Determinan Kematian COVID-19 di Wilayah Jakarta Timur Tahun 2021 - Maulida Fitria; Ngabila Salama; Thresya Febrianti (Universitas Airlangga, 2023)
Background: The Corona Virus Disease (COVID-19) pandemic, which lasted for more than a year in Indonesia, has caused various negative impacts, including rapid inter-individual transmission, followed by an increasing number of cases and even death. The total number of deaths from COVID-19 in East Jakarta from November-January 2021 was 30%. Purpose: This study aims to determine the factors that influence deaths from COVID-19 in East Jakarta. Methods: The study was conducted using a quantitative method and a case-control design with secondary data from November 2020 to February 2021 in East Jakarta. The incidence number of COVID-19 cases is 0.3 per 100,000 population, while the variables assessed were age, sex, respiratory symptoms, hypertension, cardiovascular diseases, and Chronic Obstructive Pulmonary Disease (COPD). The case sample was 74 people with COVID-19 who had died, while the control was 74 people who lived. Furthermore, the total sampling technique was used in the case group, while simple random sampling was employed in the control and data analysis was performed using the Chi-Square test. Results: Factors related to the incidence of COVID-19 death in this study were age with p-value = 0.01; OR = 3.99 95%CI 1.88 – 8.47 and male gender with p-value = 0.01; OR = 2.41 95%CI 1.25 – 4.68. Other factors analyzed, namely the presence of symptoms in the respiratory tract, comorbid hypertension, cardiovascular and COPD, did not have a significant relationship (p value> 0.05). Conclusion: Age and gender are factors associated with COVID-19 deaths in East Jakarta City between November 2020 and January 2021.